THE COUNTERING TERRORISM FINANCING AS A WAY TO PREVENT FROM INTERNATIONAL TERRORISM - Hasan Hunar Ameen Hasan; L. M. Saydulaeva; M. Yu. Shamrin (Московский журнал международного права, 2019)
Introduction. There is no doubt that nowadays the problems of countering terrorism activity are the matters of topical interest. The financing terrorism is focusing on the creation of a climate of fear and social tension in the world. So, it creates a threat to every country and individuals. The problems of financing terrorism directly or indirectly affect all countries. It is important to cooperate all forces and find more effective mechanisms to solute this problem. The international cooperation is an essential element of anti-terrorism activities.Materials and methods. The aim of the article is to explore the characteristics of this crime through the lens of the analysis of international criminal law in the field of countering the financing of terrorism. The regulatory framework of different states in the area of terrorist financing was analyzed. The described situations and problems showed the real difficulties in combating the financing of terrorism.Research results. The article includes the analysis of criminal legislation on countering the promotion of terrorist activities in the form of terrorist financing in different countries, which allows to draw certain conclusions about the essential characteristics of this crime.Discussion and conclusions. The article concludes that it is possible to exchange the experience between different countries in order to achieve the effective counter international terrorism. After highlighting the most significant problems arising in assessing the financing of terrorism, it is also possible to find out a new direction in improving the quality of counteraction to this phenomenon in general.